VroomVault: a blockchain-powered marketplace for cars and workshop services - Lim, Jing Yi (Nanyang Technological University, 2024)
This report delves into the development and exploration of VroomVault, a blockchain-based Car Marketplace designed to bridge the gap between the tangible, real-world automotive market, and the burgeoning realm of blockchain technology. Utilizing Ethereum smart contracts, the project aimed to foster transparency, security, and efficiency in car transactions, treating vehicles as non-fungible tokens (NFTs) to facilitate ownership transfer, history tracking, and trading on a decentralized platform.